Public goods, public gains calculating the social benefits of public R&D - Link, Albert N.; Scott, John T., 1947- (New York ; Oxford : Oxford University Press, 2011)
In 'Public Goods, Public Gains', the authors discuss and apply in case studies the systematic application of alternative evaluation methods to estimate the social benefits of publicly-financed research and development (R&D).
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Technological innovations -- Economic aspects; Research, Industrial -- Economic aspects; Cost effectiveness; Public goods